2020
DOI: 10.3390/molecules25102419
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Composites Based on Graphene Oxide and Polystyrene

Abstract: In this work, new optical properties of composites based on polystyrene (PS) microspheres and graphene oxide (GO) are reported. The radical polymerization of styrene in the presence of benzoyl peroxide, pentane and GO induces the appearance of new ester groups in the PS macromolecular chains remarked through an increase in the absorbance of the infrared (IR) band at 1743 cm−1. The decrease in the GO concentration in the PS/GO composites mass from 5 wt.% to 0.5 wt.% induces a diminution in the intensities of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The peaks in the range of 2000–1660 cm −1 can be attributed to monosubstituted benzene rings. The rest of the bands belong to the stretching and torsional vibrations of the C–H bonds (3081, 3058, 3025, 1069, 1028, 758, 700 cm −1 ) [ 41 ]. The difference FTIR spectrum of the composite and the PS matrix ( Figure 4 e) demonstrates only the presence of weak signals in the region of the TMSPM absorption bands [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…The peaks in the range of 2000–1660 cm −1 can be attributed to monosubstituted benzene rings. The rest of the bands belong to the stretching and torsional vibrations of the C–H bonds (3081, 3058, 3025, 1069, 1028, 758, 700 cm −1 ) [ 41 ]. The difference FTIR spectrum of the composite and the PS matrix ( Figure 4 e) demonstrates only the presence of weak signals in the region of the TMSPM absorption bands [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…These changes must be understood in terms of the appearance of some of the ClCH=CH–, CH 2 =CCl–, and/or –CH=CCl– units as a result of the partial dehydrogenation of the PVC macromolecular chains, as shown in Scheme 1 . As shown in our previous study, the main IR bands of the GO sheets are situated at 1032, 1163, 1212, 1414, 1599, 1724, and 3594 cm −1 , and they are assigned to the vibrational mode of the stretching of C=C bonds, C–O in the ether group, OH groups, the deformation of OH and COOH groups, H 2 O molecules on the GO sheet surfaces, the stretching of C=O in COOH and CHO groups, and the stretching OH in the free H 2 O molecules, respectively [ 16 , 28 ]. According to Figure 4 c,d, as the GO sheet concentration in the PVC/GO composite mass increases, the following can be observed: (i) an increase in the absorbance of IR bands peaking at 1776 and 3319 cm −1 ; (ii) a change in the ratio of the absorbances of the bands localized in the spectral ranges of 600–750 and 2750–3250 cm −1 with the maxima of IR bands of high absorbance at 611 and 2920 cm −1 , from 1.28 (black curve in Figure 4 c) to 0.36 (blue curve in Figure 4 c) when the GO concentration is equal to 0 and 5 wt.%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…An oxidative–exfoliation method in the presence of 74.7 mL H 2 SO 4 85 wt.% and 8.3 mL H 3 PO 4 85% was used for the preparation of the GO sheets [ 14 , 15 ]. Detailed information about this method can be found in our previous studies [ 14 , 15 , 16 ]. In brief, graphite powder was sonochemical exfoliated using H 2 SO 4 as solvent medium, KMnO 4 as the oxidant agent, and H 3 PO 4 as the protective agent against excessive oxidation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown significant improvements in graphene properties by doping it with different heteroatoms such as Florine (F), Oxygen (O) [ 15 ], Nitrogen (N) [ 16 ], and Boron (B) [ 17 ]. The boron-doped graphene oxide has been reported in various applications such as supercapacitor [ 18 ], Li-ion batteries [ 19 ], solar cells [ 20 ], and the enhanced photogenerated catalysis [ 21 ].…”
Section: Introductionmentioning
confidence: 99%